Studying of some physical and chemical properties of soils in villages (Kafrram, Barsheen, Al Bitar) on the basalt Sheen hill in Homs (Journal of Hama University, 2019)
The field study was conducted in (2017) in order to identifying some physical and chemical properties of soil of villages (Kafrram, Barsheen,Al Bitar) on the basalt Sheen hill area in Homs. The results were subjected to statistical analysis and test of differences in a less significant difference (L.S.D) at the probability level 5% and the calculation of the simple (SPEARMAN) correlation coefficient by which the ratio of clay, cation exchange capacity, real density and organic matter content can be predicted. Digging two soil profiles in each village, so that these profiles represent the soil of the selected villages. Samples of soil were taken from the depths (0-25, 25-50, 50-75) cm. The results showed that there was a significant correlation between the values ​​of the clay percentage  on the one hand with the cation exchange capacity values ​​and the real density values ​​on the other hand (0.78 and 0.69) respectively. The results of the statistical analysis indicated that there were significant differences between the soil properties studied in the villages where the village of Al Bitar surpassed the values ​​of cation exchange capacity, clay percentage values ​​and real density values. While the village of Barsheen surpassed the values ​​of soil organic matter.